SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE AS A PROMOTIVE AND PREVENTIVE EFFORT IN PALLIATIVE CARE FOR PEOPLE WITH DIABETES MELLITUS - Ratna Yunita Sari; Nety Mawardah Hatmanti; Abdul Muhith; Imamatul Faizah; Evi Sylvia Awwalia; Riska Rohmawati (Community Service Journal of Indonesia, 2022)
Diabetes mellitus is a progressive disease that requires long treatment and large costs with various complications that can affect the physical, psychological and spiritual so promotive and preventive efforts are needed for palliative care that can improve the quality of life for people with diabetes mellitus. The purpose of this activity is to train health cadres and the community in increasing knowledge and how to carry out treatment with the Spiritual Emotional Freedom Technique as a promotive and preventive effort in palliative care for people with DM. The method used in this community service activity is to provide training and education on health services. This activity was carried out from April-May 2022 and was attended by 15 health cadres and 50 residents in RW 05, Wonokromo Village, Surabaya. The results show that the activity has achieved success according to the success indicators that have been set, namely 15 health cadres were successfully recruited; average attendance was 100%, participants participated enthusiastically, knowledge of cadres after training and residents after counseling increased significantly.